Room‐Temperature Wide‐Gap Inorganic Materials with Excellent Plasticity - Huang, Haoran; Chen, Heyang; Gao, Zhiqiang; Ma, Yupeng; Zhao, Kunpeng; Wei, Tian‐Ran; Shi, Xun (Advanced functional materials, 2023)
In general, inorganic non‐metallic materials exhibit brittleness, and achieving plasticity in wide‐gap semiconductors or dielectrics poses an even greater challenge. Historically, silver halides have been suggested to be ductile; however, their deformability under different load modes has not been well demonstrated, and the underlying mechanisms are not fully understood. In this study, the authors demonstrate the excellent plasticity of AgCl and AgBr polycrystals at room temperature under tension, bending, compression, and roller pressing. In particular, the rolling reduction rate of AgCl/AgBr exceeds 97%, corresponding to the plastic extensibility from 3600% to 4200%. The metal‐like plasticity and multiple slip systems are attributed to the ionic features, specifically the Coulombic nature of the Ag‐Cl/Br interactions, and the appreciable polarization of the anions. Such less localized diffuse bonding can be readily switched upon atomic gliding, thus ensuring slip without cleavage. This study contributes to the advancement of the understanding and development of wide‐gap plastically deformable inorganic materials for applications in flexible, shape‐conformable high‐power electronics and dielectrics.